2020
DOI: 10.3934/neuroscience.2020022
|View full text |Cite
|
Sign up to set email alerts
|

Is there a link between depression, neurochemical asymmetry and cardiovascular function?

Abstract: Although at present depression is one of the most disabling disorders in our social environment, the understanding of its pathogenesis and the resources for its treatment are still unsatisfactory. The importance of brain asymmetry in the pathogenesis of disorders in brain function, including mood disorders such as depression, is a highly unexplored, sometimes underrated, and even ignored topic. It is important to note that the basal and pathological functional lateralization must have an underlying neurochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…There is also evidence that connects cardiovascular function, neurochemical asymmetries and depression [ 28 ]. The brain–heart axis is further implicated in post-stroke cardiovascular complications known as the stroke-heart syndrome, sudden cardiac death and the Takotsubo syndrome, amongst other neurocardiogenic syndromes.…”
Section: New Clinical and Research Applicationsmentioning
confidence: 99%
“…There is also evidence that connects cardiovascular function, neurochemical asymmetries and depression [ 28 ]. The brain–heart axis is further implicated in post-stroke cardiovascular complications known as the stroke-heart syndrome, sudden cardiac death and the Takotsubo syndrome, amongst other neurocardiogenic syndromes.…”
Section: New Clinical and Research Applicationsmentioning
confidence: 99%
“…Besides, Shinoura N et al [ 38 ] found that stress-related vascular responses were suppressed in the right cerebral hemisphere during migraine interictal periods, which indirectly suggested left-right cerebral functional asymmetry in migraine mechanisms. In addition, this functional asymmetry has been studied in other disorders, for example, antidepressants can increase activity in the left hemisphere [ 39 , 40 ], Kong XZ et al [ 41 ] have also shown that autism spectrum disorder (ASD) is associated with a subtle reduction in cortical thickness asymmetry that is widely distributed in cortical regions. Therefore, asymmetric regulation of brain function has been gradually discovered and studied in some diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic 15 O-H 2 O PET brain imaging can identify the central nervous pathways of angina pectoris, highlighting the interplay between the brain and the heart in such patients [42]. There is also evidence that connects cardiovascular function, neurochemical asymmetries and depression [43]. An 18 F-FDG PET/CT study has linked resting amygdalar activity with cardiovascular events, indicating a potential mechanism to predict risk of cardiovascular disease caused by stress [44].…”
Section: Organ Axesmentioning
confidence: 99%